Leukocyte filtration of the cardiotomy suction. Does it affect systemic leukocyte activation or pulmonary function?. (October 2017) - Issitt, Richard; Ball, Jon; Bilkhoo, Indie; Mani, Adnan; Walsh, Bronagh; Voegeli, David
Background: Cardiopulmonary bypass is thought to propagate a global systemic response through contact with the non-physiological surfaces of the extracorporeal circuit, leading to the stimulation of leukocytes, their adherence to endothelial cells and the release of cytotoxic molecules. This, in turn, has been shown to accelerate pulmonary injury. This study tested a new leukocyte-filtration system (RemoweLL) against a conventional system with no leukocyte-depleting capacity to determine the efficacy of the filtration system and its effects on pulmonary function. Methods: Thirty patients underwent coronary artery bypass graft surgery using either the RemoweLL filtration system (15 patients) or a conventional cardiopulmonary bypass circuit (15 patients). Data were collected on the total number of leukocytes, their differentiation and activation, using the leukocyte adhesion integrin CD11b as a surrogate marker. Pulmonary function was assessed using the Alveolar-arterial Oxygenation Index (AaOI) and patients were categorized using the Berlin definition of acute respiratory distress syndrome (ARDS). Results: Both groups showed significant increases in leukocyte numbers during CPB (p<0.001), with no differences noted between the groups. CD11b showed a significant increase in both groups, with peak activation occurring at the end of CPB, but no difference between the groups (p=0.8). There was a trend towards lower AaOI increases in the filtration group, but this did not reach significance (p=0.075) and there was no difference in ARDS definitions (p=0.33). Conclusions: Leukocyte filtration of cardiotomy suction did not influence total leukocyte counts or activation as measured by CD11b upregulation. Furthermore, no evidence could be found to suggest improved pulmonary function.